Accentuation in the Ukrainian version of church Slavonic language and its display in works of H. Skovoroda and T. Shevchenko - Hnatiuk, Lidia (Ukrainian linguistics, 2017)
The article summarizes I. Ohienko’s observations regarding peculiarities of accentuation in the Ukrainian version of Church Slavonic language of the 16th–17th centuries, which was completely different from the Russian version of Church Slavonic language in terms of pronunciation. The most important differences between the two versions are the following: in nominal parts of the language the stress falls on the root in the Ukrainian version of Church slavonic language while in the Russian version it’s on the inflexion, in participles and adjectives of the Ukrainian version the stress falls on the suffix -enn, -ann, and in the Russian version – on the root or other suffix. The paper shows continuation of Old Ukrainian bookish tradition in the language practice of Н.  Skovoroda and T. Shevchenko. Information about the author:Lidiia Hnatiuk – Dr Hab, Prof. of the Department of the Ukrainian Language and Applied Linguistics; Institute of Philology; Taras Shevchenko National University of Kyiv (Ukraine).E-mail: lidahnatjuk@gmail.com__________References• Veselovs’ka Z.M. (1970) Naholos u skhidnoslovyans’kykh movakh pochatkovoyi doby formuvannya rosiys’koyi, ukrayins’koyi ta bilorus’koyi natsiy (kinets’ XVI – pochatok XVIII st.) [Stress in the East Slavic languages in an initial stage of formation of Russian, Ukrainian and Belarusian nations (late 16th – early 18th century)]. Kharkiv: Vyd-vo Kharkiv. un-tu, 163 р. (in Ukrainian).• Hal’chuk I.Yu. (2008) Naholos hramatyky M.Smotryts’koho yak vidbyttya staroukrayins’koyi aktsentnoyi systemy [Stress of M.Smotrytskyi’s grammar as a display of Old Ukrainian accentuation system]. Linguistics, no. 4/5, pp. 79-91 (in Ukrainian).• Zhovtobryukh M. A. (1972) Vidbyttya protsesu stanovlennya fonolohichnoyi systemy ukrayins’koyi literaturnoyi movy u tvorakh H.Skovorody [Display of the process of formation of phonological system in Ukrainian literary language in works of Н.Skovoroda]. Linguistics, no. 4, pp. 59-70 (in Ukrainian).• Zynyakova A. A. (1996) Naholoshennya imennykiv zhinochoho rodu na -a, -ya v “Eneyidi” I.Kotlyarevs’koho [Stressing of nouns of feminine gender of -a, -ya in I.Kotliarevskyi’s “Eneyida”]. Skhidnoslovyans’ki movy v yikh istorychnomu rozvytku: zb. nauk. pr. [East Slavic languages in their historical development: Collected papers]. Zaporizhzhya, part 2, pp. 2-25 (in Ukrainian).• Zynyakova A.A. (1995) Naholoshennya imennykiv seredn’oho rodu na -o, -e v “Eneyidi” I.Kotlyarevs’koho [Stressing of nouns of neuter gender of -o, -ein I. Kotliarevskyi’s “Eneyida”]. Linguistics, no. 2, pp. 38-47 (in Ukrainian).• Ohiyenko I. (1995) Istoriya ukrayins’koyi literaturnoyi movy [Нistory of Ukrainian literary language]. Kyiv: Lybid’, 293 p. (in Ukrainian).• Ohiyenko I. (1932) Lyseyivs’ka triod’ 1734 roku : z istoriyi ukr. movy v XVIII vitsi [Lyseyivs’ka triod’ of 1734: from the history of Ukrainian language in the 18th century]. Varshava: druk. Synodal’na, 34 p. (in Ukrainian).• Ohiyenko I. (1925) Naholos yako metod oznachennya mistsya vykhodu starodrukovanykh knyzhok: zamitky z istoriyi naholosu na posluhakh paleotypiyi [Stress as a method of defining places of publication of early printed books: notes about the history of stress for the needs of palaeotypy]. Proceedings of Taras Shevchenko Scientific Society, vol. 136/137, pp. 197-224 (in Ukrainian).• Ohiyenko I. (1930) Ukrayins’ka literaturna mova XVI-host. i ukrayins’kyy Krekhivs’kyy Apostol [Ukrainian literary language of the 16th cent. and Ukrainian Krekhivs’kyy Apostol].Varshava: Drukarnya synodal’na, vol. I, 520 p. (in Ukrainian).• Ohiyenko I. (1952) Ukrayins’kyy literaturnyy naholos [Ukrainian literary stress].Vinnipeh: The Christian Press, 303 p. (in Ukrainian).• Ohiyenko I. (1926) Ukrayins’kyy naholos na pochatku XVII viku [Ukrainian stress in the early 17th century]. Zhovkva: ChSVV, 31 p. (in Ukrainian).• Ohiyenko I. (1928) Ukrayins’kyy naholos u XVI vitsi [Ukrainian stress in the 16thcentury]. Collection of the Department of Russian Language and Literature of the Academy of Sciences of the USSR, Leningrad, vol. 101, no 3, pp. 444-451 (in Ukrainian).• Čyževskyj D. (1934) Literarische Lesefrűchte: Zur Sprache Skovorodas. Zeitschrift für slavische Philologie, vol. 11, pp. 21-22 (in German).
Keywords: history of Ukrainian accentuation, Old Ukrainian bookish tradition, Ukrainian system of accentuation, Ukrainian version of Church Slavonic language, Russian version of Church Slavonic language